Factors limiting seed germination of terrestrial bromeliads in the sandy coastal plains (restinga) of Maricá, Rio de Janeiro, Brazil - André Mantovani; Ricardo Rios Iglesias (Rodriguésia)
ABSTRACT Vegetation islands surrounded by bare sand are one of the most characteristic features of the sandy plains (restinga) of the Brazilian coastline. Abiotic conditions outside the islands are too harsh for the establishment of plants. Bromeliads are frequent both inside and at the borders of islands, but infrequent outside the islands in the restinga of Maricá. We hypothesized that the rarity of bromeliad seedlings in the restinga is due to high mortality during the seed and/or seedling stages. In this study, we assessed the potential limiting factors for germination and seedling survival of three terrestrial bromeliads Neoregelia cruenta, Aechmea nudicaulis and Vriesea neoglutinosa. Seed viability, water balance during dry-wet cycles, germination under different water potentials and the susceptibility of seedlings to high temperatures, desiccation and sand burial were analyzed. The tested seeds were nondormant, and they germinated to >70% even after exposure to 60ºC and desiccation. At temperatures > 27ºC, seeds lost water faster than imbibited it, and drywet cycles and water potentials of -0.4 MPa decreased germination. Thus, low water availability is likely limiting factor for bromeliad seed germination in the restinga of Maricá. Seedlings were extremely sensitive to high temperatures and sand burial. Shoots failed to emerge if seed depth exceeded 10 mm. We suggest that unequal temporal distribution of rainfall, low water retention capacity of the soil, and high temperatures inhibit germination and seedling establishment through water stress. Consequently, bromeliads are not likely to act as pioneer plants in the barren regions that separate restinga islands.